How to Make Public Works Work : A Review of the Experiences - del Ninno, Carlo (World Bank, Washington, DC, 2012)
Public work programs (PWPs) have been an important safety nets instrument used in diverse country circumstances at different points in time in both middle income and low income countries. Well-designed and implemented PWPs can help mitigating income shocks; the programs can also be used to reduce poverty. This paper reviews the experience with PWPs in several countries over the past 20 years to delineate use patterns and to determine the factors contributing to its use as a successful safety net program. This is done by reviewing cross-country variations in the design, implementation procedures and delivery models followed by an assessment of methods for monitoring and evaluation specific to public works.